Methodological approaches to monitoring erosion of agricultural lands in the European part of Russia by using satellite imagery - O.P. Yermolaev; R.A. Medvedeva; E.V. Platoncheva (Учёные записки Казанского университета: Серия Естественные науки)
Erosion is the main process of soil cover degradation in agricultural lands. Among all erosion processes, linear (rill and gully) erosion is the most unfavorable one. Assessment of linear erosion dynamics in the area of intensive agriculture in the European part of Russia is important due to the absence of any generalized data on its development during the post-Soviet period. The advance in information technologies, appearance of satellite images with high and very high resolution allow to successfully solve the task of analysis of the current gully dissection, dynamics of gullies, and identification of zones of rill erosion in arable lands. The paper focuses on the methodological aspects of the use of satellite images for estimation of modern dynamics of rill and gully erosion. Gully dissection has been analyzed by the identification of the indicators of gully density, as well as the areal and linear dynamics of gully network. The maps of gully network density have been elaborated for five key basins. A new method has been developed for geoinformation mapping of rill erosion belt dynamics. We have also suggested a system of indicators that quantitatively characterize erosion development on arable slopes.